Comparison of laparoscopic Toupet and laparoscopic Nissen fundoplications in neurologically normal children. Issue 2 (20th September 2017) - Miyano, Go; Yamoto, Masaya; Miyake, Hiromu; Kaneshiro, Masakatsu; Morita, Keiichi; Nouso, Hiroshi; Koyama, Mariko; Okawada, Manabu; Doi, Takashi; Koga, Hiroyuki; Lane, Geoffrey J; Fukumoto, Koji; et al.
Abstract: Introduction: We compared laparoscopic Toupet fundoplication (LTF) and laparoscopic Nissen fundoplication (LNF) in neurologically normal children. Methods: Forty neurologically normal children who were followed up for more than 3 years after LTF ( n = 22) or LNF ( n = 18) were reviewed retrospectively. LTF and LNF were performed between 2006 and 2012. Results: There were no significant differences in gender (LTF, 15 male and 7 female patients; LNF:, 12 male and 6 female patients), mean age at surgery (LTF vs LNF: 2.5 vs 2.3 years), mean weight at surgery (LTF vs LNF: 9.6 vs 8.9 kg), preoperative symptoms, preoperative pH monitoring (pH <4) (LTF vs LNF: 26.7% vs 21.8%), mean operative time (LTF vs LNF: 117 vs 126 min), postoperative recommencement of enteral feeding (LTF vs LNF: 3.7 vs 3.8 days), or duration of hospitalization (LTF vs LNF: 5.5 vs 6.3 days). Intraoperative complications were esophageal trauma (LTF; n = 1; 4.5%) and liver trauma (LNF; n = 1; 5.6%) ( P = 0.70). Post‐LTF complications were wrap stenosis ( n = 1; 4.5%), and post‐LNF complications were wrap stenosis ( n = 1; 5.5%) and gastric outlet obstruction ( n = 1; 5.5%) ( P = 0.43); all were managed conservatively. No case required conversion to open repair. There was no recurrence after LTF, but there were three cases (16.7%) after LNF ( P = 0.08). Reoperation was performed at 4, 11, and 13 months, respectively. Conclusion: Despite LTF and LNF appearing to be equally effective, three LNF cases required reoperation.